FENOMENA BIMBINGAN BELAJAR DI KALANGAN SISWA MADRASAH - Nurul Lailatul Aulia; Fitri Shofiatul Ulul Hikmah; Achmad Habibi; Rifqi Khairul Anam (As-Sulthan Journal of Education, 2026)
The increasing number of madrasah students participating in private tutoring (bimbel) is a response to the dynamics of academic competition and educational mobility, which have become increasingly competitive. This article aims to analyze various factors driving student participation through the lens of social reality construction using a literature review method. The results of the study indicate that students' decisions are influenced by a complex interaction between social and academic factors. Socially, participation is triggered by parental expectations that view private tutoring as a future investment, peer pressure that establishes